Preparation method of sulfur-doped black phosphorus-carbon composite negative electrode material
Through the preparation method of sulfur-doped black phosphorus-carbon composite negative electrode material, the problem of capacity attenuation caused by volume expansion in lithium-ion batteries is solved, and the cycle stability and rate performance is achieved, meeting the energy density needs of new energy vehicles.
Patent Information
- Application Number
- CN202411636312.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
AI Technical Summary
Black phosphorus expands severely during the circulation of lithium-ion batteries, resulting in rapid attenuation of capacity, limiting its development and application in batteries.
The preparation method of sulfur-doped black phosphorus-carbon composite negative electrode material is adopted. By mixing the carbon material with the sulfur material and the sulfur material, ball milling and vacuum heat treatment are carried out to form a composite of sulfur-doped carbon material and black phosphorus, which enhances the structural stability and electrical conductivity of the material.
It significantly improves the cycle stability and rate performance of lithium-ion batteries, extends the service life of the battery, and meets the energy density needs of new energy vehicles.
Smart Images

Figure CN119601617A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a sulfur-doped black phosphorus-carbon composite negative electrode material, and belongs to the technical field of performance optimization of negative electrode materials for lithium ion batteries. Background Art As energy depletion and environmental pollution become increasingly serious, lithium-ion batteries, as a clean energy with high energy density, have been widely used in mobile electronic devices such as mobile phones, computers and electric vehicles.
[0002] The negative electrode material is an important component of lithium-ion batteries, and its performance directly determines the performance of lithium-ion batteries. Currently, the most common commercial negative electrode material is graphite, but due to its low theoretical specific capacity (372 mAh / g), it is difficult to meet the needs of social development, making people urgently look for new alternative negative electrode materials. Black phosphorus has an extremely high theoretical capacity (2592 mAh / g) and good conductivity, and is expected to become a new generation of negative electrode materials for lithium-ion batteries.
[0003] However, the dramatic volume expansion of black phosphorus during the cycle (up to 200%) will lead to rapid capacity decay, which seriously limits its development and application in ion batteries. The traditional ball milling process can improve battery performance by combining black phosphorus with carbon materials, but the resulting composite material structure is mostly unstable. After continuous charge and discharge, the battery cycle performance will still decay rapidly due to the volume expansion of black phosphorus, making it difficult to achieve industrial application. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies mentioned in the technical background and provide a method for preparing a sulfur-doped black phosphorus-carbon composite negative electrode material.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a sulfur-doped black phosphorus-carbon composite negative electrode material comprises the following steps: (1) uniformly mixing the carbon material and the sulfur material, and placing the mixed material in a ball mill filled with ball milling beads in an inert atmosphere for ball milling; (2) sealing the carbon material after ball milling in step (1) in a vacuum quartz tube for vacuum heat treatment; (3) The sulfur-doped carbon material after vacuum heat treatment in step (2) is uniformly mixed with the black phosphorus powder and placed in a ball mill filled with ball milling beads in an inert atmosphere for ball milling.
[0006] (4) The product of ball milling in step (3) is sieved under an inert atmosphere to obtain a sulfur-doped black phosphorus-carbon composite negative electrode material.
[0007] In the above preparation method, preferably, the carbon material in step (1) is selected from one or more of graphite, carbon nanotubes, hard carbon and glassy carbon.
[0008] In the above preparation method, preferably, the sulfur material in step (1) is selected from one or more of sulfur powder, thioacetamide and thiourea.
[0009] In the above preparation method, preferably, the mass of the sulfur material in step (1) accounts for 0.1%-30% of the total mass.
[0010] In the above preparation method, preferably, the diameter of the ball milling beads in step (1) is 1-20 mm, the filling rate of the ball milling jar is 1%-80%, and the ball-to-material ratio is 40:1-100:1.
[0011] In the above preparation method, preferably, the ball milling speed in step (1) is 10-400 rpm, and the ball milling time is 0.1-20 h.
[0012] In the above preparation method, preferably, the vacuum heat treatment temperature in step (2) is 200-1200° C., and the heat treatment time is 1-24 h.
[0013] In the above preparation method, preferably, the mass of the black phosphorus powder in step (3) accounts for 50%-90% of the total mass.
[0014] In the above preparation method, preferably, the diameter of the ball milling beads in step (3) is 1-20 mm, the filling rate of the ball milling jar is 1%-80%, and the ball-to-material ratio is 40:1-100:1.
[0015] Preferably, the diameter of the ball milling beads in step (3) is 1-20 mm, and the ball milling beads (zirconia balls) of 12-20 mm, 6-10 mm and 1-5 mm are mixed in a mass ratio of 1: (1.5-2.5): (3-6); more preferably, the ball milling beads (zirconia balls) of 15 mm, 8 mm and 5 mm are mixed in a mass ratio of 1:2:4.
[0016] In the above preparation method, preferably, the ball milling speed in step (3) is 100-800 rpm, and the ball milling time is 1-50 h. Compared with the prior art, the advantages of the present invention are: (1) The present invention breaks through the current limitation of the low theoretical capacity of graphite negative electrodes and develops a sulfur-doped black phosphorus-carbon composite negative electrode material. The reversible specific capacity can reach more than three times that of graphite negative electrodes. It can be used to replace conventional graphite negative electrodes, effectively improve the energy density of lithium-ion batteries, and meet the development needs of new energy vehicles.
[0017] (2) The present invention will adopt the method of ball milling the carbon material and the sulfur material and then performing vacuum heat treatment, which can not only make the sulfurization of the material more uniform, but also produce nanopores and defects in the carbon skeleton as the sulfur volatilizes and releases during the high-temperature carbonization process, thereby increasing the surface area and the disorder of the carbon material crystallites, thereby providing additional lithium storage sites through adsorption of pores and defects.
[0018] (3) The present invention ball-mills black phosphorus and sulfur-doped carbon materials to compound, which can not only improve the conductivity of black phosphorus, but also form phosphorus-carbon, phosphorus-sulfur and carbon-sulfur chemical bonds, thereby enhancing the structural stability of the material.
[0019] (4) The present invention uses sulfur elements with a larger atomic radius for doping, which can increase the material layer spacing, which is beneficial to the insertion / extraction and diffusion of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the EDS data of the CS material in Example 1.
[0021] Figure 2 This is a comparison chart of the cycle stability performance of BP-CS and BP-C sample button half-cells at 0.5C in Example 1 and Comparative Example 1.
[0022] Figure 3 It is a comparison chart of the rate performance of BP-CS and BP-C sample button half-cells in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0026] Example 1 A method for preparing a negative electrode material for a lithium ion battery by using sulfur-doped black phosphorus-carbon, comprising the following steps: 1) First, add 3 wt.% sulfur powder to the graphite and mix evenly. Then, place the mixed material in a 125 mL zirconia ball mill, add 5 mm zirconia balls with a filling rate of 60%, and ball mill at a speed of 100 rpm for 1 h under argon atmosphere; 2) The ball-milled material was sealed in a vacuum quartz tube and subjected to vacuum heat treatment at 900°C for 6 h; 3) The heat-treated carbon material (CS) and black phosphorus powder were uniformly mixed in a mass ratio of 3:7 and placed in a 500 mL zirconia ball mill. Then, 15 mm, 8 mm and 5 mm zirconia balls were added to the stainless steel tank in a mass ratio of 1:2:4 to ensure that the ball-to-material mass ratio was 80:1. At the same time, the filling rate of the zirconia tank reached 60% and the tank was filled with argon atmosphere. After ball milling at a speed of 350 rpm for 24 h; 4) The ball-milled product in step (3) was sieved under an argon atmosphere to obtain sample BP-CS.
[0027] Comparative Example 1 The black phosphorus and graphite powders were evenly mixed in a mass ratio of 7:3 and placed in a 500 mL zirconia ball mill. Then, 15 mm, 8 mm and 5 mm zirconia balls were added to the stainless steel tank in a mass ratio of 1:2:4 to ensure that the ball-to-material mass ratio was 80:1. At the same time, the filling rate of the zirconia tank reached 60% and the tank was filled with argon atmosphere. After ball milling at 400 rpm for 24 h, the sample BP-C was sieved.
[0028] like Figure 1 As shown, it is the EDS data of CS material. From the data, it can be seen that a small amount of sulfur element is successfully and evenly incorporated into the carbon material, and no other impurities are introduced.
[0029] like Figure 2 As shown in the figure, it is a comparison of the cycle stability performance of BP-CS and BP-C sample button half-cells at 0.5C. It can be seen from the figure that the initial reversible specific capacities of BP-CS and BP-C are both above 1200 mAh / g, and the cycle stability of BP-CS is significantly better than that of BP-C. The capacity retention rate of BP-CS after 100 cycles reaches 95.02%, while the capacity retention rate of BP-C after 100 cycles is only 0.07%, indicating that sulfur doping can indeed improve the structural stability of the phosphorus-carbon negative electrode.
[0030] like Figure 3As shown in the figure, it is a comparison of the rate performance of BP-CS and BP-C sample button half-cells. It can be clearly seen from the figure that the rate performance of BP-CS is also significantly better than that of BP-C. The capacity retention rate of BP-CS at 3C is 75.50%, while the capacity retention rate of BP-C at 3C is only 60.66%, indicating that sulfur doping can also increase the interlayer spacing of phosphorus-carbon materials, which is beneficial to the insertion / extraction of lithium ions, so as to improve the rate performance of the material.
[0031] Example 2 Based on Example 1, the addition amount of sulfur powder in step 1) was changed to 1% and 6% respectively, and the rest was the same as Example 1. The results are shown in Table 1. It can be seen from the test data that the cycle and rate performance of the battery are best when the sulfur content is added to 3%. When the addition amount is 1%, the sulfur doping amount is too low, too few SC and SP bonds are formed, and the material interlayer spacing is not widened thoroughly, so the cycle and rate performance cannot reach the optimal value; when the addition amount is 6%, the sulfur doping amount is too high. Although the cycle performance is also significantly improved, impurities are easily introduced during the high-energy ball milling process, which is not conducive to the performance of the rate performance.
[0032] Table 1
[0033] Example 3 Based on Example 1, step 1) was changed to a different sulfur raw material, 10 g of graphite powder was placed in 100 mL of 1 mol / L sulfuric acid aqueous solution, stirred for 1 hour, and then filtered, and then the filtered graphite powder was vacuum dried at 120° C. for 5 hours. The rest was the same as Example 1.
[0034] Table 2
[0035] From the comparison in Table 2, it can be seen that the capacity and cycle performance of the phosphorus-carbon negative electrode material after sulfurization with solid sulfur powder are significantly better than those with liquid sulfuric acid. This is because the material will be partially oxidized during the sulfuric acid sulfurization process, which aggravates the instability of the material and causes a significant decrease in material performance.
[0036] Example 4 Based on Example 1, the conditions of the ball milling beads were changed in step 3), and single 5 mm and 15 mm zirconium balls were used for ball milling respectively. The rest was the same as Example 1.
[0037] Table 3
[0038] From Table 3, we can see that the effects of high-energy ball milling with zirconium balls of different sizes are quite different. The best effect is achieved by mixing large, medium and small sizes, while the performance of single 5 mm or 15 mm zirconium balls is not ideal. This is because when the diameter of the ball milling bead is too small, the energy generated by the impact during the ball milling process is small, making it difficult for P to bond with C and S, and the cycle stability is significantly reduced; when the diameter of the ball milling bead is too large, the gap between the balls will also be larger, which will cause uneven ball milling between the powders and lead to poor performance.
[0039] Comparative Example 2 Based on Example 1, step 2) is not performed, and the rest is the same as Example 1.
[0040] Table 4
[0041] It can be seen from Table 4 that after the vacuum high-temperature calcination step was omitted in Comparative Example 2, due to insufficient sulfurization, it was difficult to form more bonds between sulfur, carbon and phosphorus, and most of them were just physical blending, so the cycle and rate performance decreased significantly.
[0042] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.
[0043] The above is only a specific implementation of the present invention. It should be pointed out that for R&D technicians in this field, without departing from the principle of the present invention, they can make several improvements and modifications, which should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material for a lithium-ion battery by using sulfur-doped black phosphorus-carbon, characterized in that: The preparation method steps are as follows: (1) mixing the carbon material and the sulfur material, and placing the mixed material in a ball mill filled with ball milling beads in an inert atmosphere for ball milling; (2) sealing the carbon material after ball milling in step (1) in a vacuum quartz tube for vacuum heat treatment; (3) uniformly mixing the sulfur-doped carbon material after vacuum heat treatment in step (2) with the black phosphorus powder and placing the mixture in a ball mill filled with ball milling beads and filled with an inert atmosphere for ball milling; (4) The product of ball milling in step (3) is sieved under an inert atmosphere to obtain a sulfur-doped black phosphorus-carbon composite negative electrode material.
2. The method for preparing a negative electrode material for a lithium-ion battery using sulfur-doped black phosphorus-carbon according to claim 1, characterized in that: The carbon material in step (1) is selected from one or more of graphite, carbon nanotubes, hard carbon and glassy carbon; The sulfur material is selected from one or more of sulfur powder, thioacetamide and thiourea.
3. The preparation method according to claim 2, characterized in that: The mass of the sulfur material in step (1) accounts for 0.1%-30% of the total mass.
4. The preparation method according to claim 1, characterized in that: The diameter of the ball milling beads in step (1) is 1-20 mm, the filling rate of the ball milling jar is 1%-80%, and the ball-to-material ratio is (40-100):
1.
5. The preparation method according to claim 1, characterized in that: The ball milling speed in step (1) is 10-400 rpm, and the ball milling time is 0.1-20 h.
6. The preparation method according to claim 1, characterized in that: The vacuum heat treatment temperature in step (2) is 200-1200° C., and the heat treatment time is 1-24 hours.
7. The preparation method according to claim 1, characterized in that: The mass of the black phosphorus powder in step (3) accounts for 50%-90% of the total mass.
8. The preparation method according to claim 1, characterized in that: The diameter of the ball milling beads in step (3) is 1-20 mm, the filling rate of the ball milling jar is 1%-80%, and the ball-to-material ratio is (40-100):
1.
9. The preparation method according to claim 1, characterized in that: The diameter of the ball milling beads in step (3) is 1-20 mm, and the ball milling beads of 12-20 mm, 6-10 mm and 1-5 mm are mixed in a mass ratio of 1: (1.5-2.5): (3-6); preferably, the ball milling beads of 15 mm, 8 mm and 5 mm are mixed in a mass ratio of 1:2:
4.
10. The preparation method according to claim 1, characterized in that: The ball milling speed in the step (3) is 100-800 rpm, and the ball milling time is 1-50 h.
Citation Information
Cited By
Preparation method of glycinate modified black phosphorus-carbon material and lithium ion battery negative electrode material
CN121460527A
Preparation method and application of secondary ball-milled sulfur-doped phosphorus-carbon negative electrode material
CN121687891A
Sulfur-doped porous carbon, phosphorus-carbon composite material and application thereof
CN122068031A
Sulfur-doped porous carbon and phosphorus-carbon composite materials and their applications
CN122068031B
Interface bonding type nitrogen-sulfur co-doped black phosphorus / MXene composite negative electrode material and preparation method and application thereof
CN122930808A